PELAKSANAAN PENEGAKAN HUKUM DESERSI DI LINGKUNGAN TENTARA NASIONAL INDONESIA OLEH POLISI MILITER (STUDI KASUS DI DETASEMEN POLISI MILITER I/3 PEKANBARU). - Silitonga, Frans Bragent; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Criminal acts can occur anywhere and at any time, including in the Indonesian National Army or what we often call with the TNI. TNI built and developed with soul disciplined and obedient to the command of the military as a tool based on the interests of the state in the field of defense and duties, not escape from an act in violation of the law, especially a military offense. One military offense that often occur in the military environment is a criminal offense of desertion. Criminal offense of desertion is a serious concern among military and law enforcement, especially the Military Police. In this case the role of the Military Police as law enforcement course is expected to run for the sake of justice in society, especially among militaryWith the above description, the authors are interested in doing research with the title Implementation of Environmental Law Enforcement National Army Indonesia Desertion By Military Police (Case Studies in Military Police Detachment I/3 Pekanbaru). This thesis aims as follows, namely to investigate, to find out the constraints faced, the latter aims to determine the effort in overcoming barriers to the implementation of law enforcement desertion in the Indonesian National Army Military Police in Regional law Military Police Detachment I/3 Pekanbaru.In writing this, the author uses empirical approach or sociological research. The location of research is in the area of Law Military Police Detachment I/3 Pekanbaru. Data sources supported by the data source of primary, secondary and tertiary. While data collection techniques are interviews / interview and review of data using deductive method is to analyze the problems of a general nature and then drawn to a conclusion in particular based on existing theory.The results of the discussions in this paper is, first, that the enforcement of environmental law in the military desertion conducted by the Military Police not running optimally. Second, the barriers faced by military police, among others, is a habit or culture of the military itself, the problem of infrastructure, and lack of law enforcement personnel.. Third, prevention efforts undertaken by the Military Police is, law enforcement professionals and high integrity, to cooperate with the community and civil law enforcement officials, conduct legal counseling, adequate facilities and infrastructure.Keywords: implementation, enforcement, desertion, military police